Resting-state fMRI functional connectivity and mindfulness in clinical and non-clinical contexts: A review and synthesis - Sezer, Idil; Pizzagalli, Diego A.; Sacchet, Matthew D. (Neuroscience and biobehavioral reviews, 2022)
This review synthesizes relations between mindfulness and resting-state fMRI functional connectivity of brain networks. Mindfulness is characterized by present-moment awareness and experiential acceptance, and relies on attention control, self-awareness, and emotion regulation. We integrate studies of functional connectivity and (1) trait mindfulness and (2) mindfulness meditation interventions. Mindfulness is related to functional connectivity in the default mode (DMN), frontoparietal (FPN), and salience (SN) networks. Specifically, mindfulness-mediated functional connectivity changes include (1) increased connectivity between posterior cingulate cortex (DMN) and dorsolateral prefrontal cortex (FPN), which may relate to attention control; (2) decreased connectivity between cuneus and SN, which may relate to self-awareness; (3) increased connectivity between rostral anterior cingulate cortex region and dorsomedial prefrontal cortex (DMN) and decreased connectivity between rostral anterior cingulate cortex region and amygdala region, both of which may relate to emotion regulation; and lastly, (4) increased connectivity between dorsal anterior cingulate cortex (SN) and anterior insula (SN) which may relate to pain relief. While further study of mindfulness is needed, neural signatures of mindfulness are emerging. •Mindfulness decreases default mode network and frontoparietal network connectivity.•Attention control relates to posterior cingulate and dorsolateral prefrontal cortex coupling.•Self-awareness relates to decreased connectivity between cuneus and salience network.•Emotional regulation aspect of mindfulness is linked to corticolimbic modulation.•Pain relief relates to coupling between dorsal anterior cingulate and salience network.